Real time nitrogen and irrigation management for enhanced productivity and nutrient use efficiency of maize under conservation agriculture - Sandeep Kumar; Vinod Kumar Singh; Kapila Shekhawat; Pravin Kumar Upadhyay; Sanjay Singh Rathore; Rishbh Kumar Didawat (Annals of Agricultural Research, 2022)
A field experiment was conducted at research farm of ICAR–Indian Agricultural Research Institute, New Delhi, India, during kharif season 2019, to find the effect of real time nitrogen (Green Seeker based) management and depletion of available soil moisture (25%) under CA on yield and NPK uptake of maize. On a splitsplit plot design; 02 crop establishment techniques (CET) viz. conservation agriculture (CA) and conventional tillage (CT) were assigned in main plots; 03 irrigation regime (IR) in sub-plots; W1 (irrigation at critical growth stages), W2 (irrigation at 25% DASM; depletion of available soil moisture), W3 (irrigation at 50% DASM), and 4 levels of nitrogen(N) in sub-sub plots; No (no-N applied), N1 (33% N as basal, 33% N at knee high stage and 34% N at silking stage), N2 (50% N basal + rest N as guided by Green Seeker (GS), N3 (75% as basal + rest N as guided by GS). Total N, P & K uptake, N use and yield of maize varied significantly due to GS based N management, irrigation at 25% DASM and CA. Highest grain yield was obtained under CA (6.05 t ha-1), W2 (6.36 t ha-1) and N3 (6.9 t ha-1) over other CET, IR and N management practices, respectively.